Nursing of a patient with wound ulceration and infection secondary to crushing injury of the left dorsalis pedis (1例左足背碾压后继发伤口破溃感染的护理体会) - DONG Pan (董攀) (Association of Integrative Nursing, 2023)
To summarized the experience of nursing of a patient with wound ulceration and infection secondary to crushing injury of the left dorsalis pedis. A Multidisciplinar team was established to develop an individualized care plan for the patent. Based on the TIME principle and moist healing theory, specialist nurse used new type of dressing to accelerate the wound healing and reduce the pain. The psychological nurse conducted the distress screening and solution focused approach to relieve the mental distress of the patient. (本文总结1例左足背碾压后继发伤口破溃感染的护理经验。多学科协作制定个体化的护理方案, 由伤口专科护士主导, 基于TIME原则和湿性愈合理论, 使用新型敷料, 促使伤口快速愈合、减轻患者疼痛; 由心理专科护士主导进行心理痛苦筛查, 运用焦点解决干预模式, 缓解患者的心理痛苦, 促进积极转变。)